Ecuador: determinantes de la deuda externa durante la pandemia covid-19. - Basantes Garcia, Marco Antonio; Betancourt Medina, Kevin Paul (Machala : Universidad Técnica de Machala, 2022)
The objective of this degree work was to identify the determinants of external debt through statistical information and its economic effect during the Covid-19 pandemic. In order to know the contrast of the determinants, we analyzed from 2018 to 2020. The method used in this research is quantitative since the results presented are descriptive statistics. The techniques and instruments used are in correspondence to a descriptive analytical approach, and for the collection of indexed data we resorted to official statistical sources such as: The World Bank, Central Bank of Ecuador and the Ministry of Economy and Finance. In order to know that the creditors and tax collection are the determinants that established the information collected, demonstrating that the economic effects of the loss of income caused by the Covid-19 pandemic had an impact on the increase of the Ecuadorian external debt by generating an imbalance with the negotiation of the debt.
El presente trabajo de titulación tuvo como objetivo identificar las determinantes de la deuda externa mediante información estadística y su efecto económico durante la pandemia Covid-19. Para conocer el contraste de los determinantes se analizó desde el año 2018 al 2020. El método utilizado en esta investigación es cuantitativo puesto que los resultados presentados son estadísticos descriptivos. Las técnicas e instrumentos que se utilizaron son en correspondencia a un enfoque analítico descriptivo, y para la recolección de datos indexados se recurrió a fuentes estadísticas oficiales como: el Banco Mundial, Banco Central del Ecuador y el Ministerio de Economía y Finanzas. Para de esta manera poder conocer que los Acreedores y la Recaudación tributaria son los determinantes que establecieron la información recolectada, demostrando que los efectos económicos en la pérdida de ingresos ocasionados por la pandemia Covid-19 incidió en el aumento de la deuda externa ecuatoriana al generar un desequilibrio con la negociación de la deuda.
Keywords: DEUDA EXTERNA; COVID-19; EFECTOS ECONOMICOS; ACREEDORES